Fouling and its mitigation on heat exchanger surfaces by additives and catalytic materials / Teng Kah Hou - Teng , Kah Hou (2018)
Calcium carbonate (CaCO3) fouling is the most commonly observed fouling phenomenon in cooling water applications. Fouling happens when a process uses cooling water supersaturated with mineral salt crystals (i.e. hard water). Precipitation deposits on heat transfer surfaces whenever these inversely-soluble salt crystals, like dissolved calcium ions, are exposed to high temperature. An online-monitoring system for fouling phenomena was studied experimentally using a mixture of sodium bicarbonate and calcium chloride for carbonate fouling salt in de-ionized water. The effects of different parameters such as surface temperature, flow velocity, and concentration on the calcium carbonate scale formation process were experimentally investigated by using the developed monitoring system. The calcium carbonate deposition rates on five different metal surfaces (Stainless steel 316, brass, copper, aluminum and carbon steel) were investigated. The surface was analyzed by analytical microscopy to investigate the morphology of the deposit layer. The results revealed that SS316 yielded the lowest deposition on the surface. Nowadays, hazardous chemical additives are often used to mitigate fouling but chemicals are expensive and pose problems to the environment. Physical water treatment (PWT), a non-chemical method is good alternative for fouling mitigation method. PWT using zinc and tourmaline as catalytic materials is presented in this research work. Fouling tests were conducted for verification of this PWT method. Artificially-hardened water at 300 mgL-1 was utilized as the fluid medium to form fouling deposits. The hard water flow velocities were varied from 0.15 ms-1 to 0.45 ms-1 and the artificially-hardened water temperature was maintained at 25 oC and the experimental time was set to 72 hours for each run. The results revealed that in the PWT-treatment case, the deposition of calcium carbonate particle is lower compared to those in the No-treatment case. Furthermore, mitigation of calcium carbonate fouling by applying EDTA, EDTA-MWCNT and DTPA-MWCNT-based water nanofluids on heat exchanger surfaces were reported. Investigation of additive (benign to the environment) on the fouling rate of deposition was performed. Assessment of the deposition of calcium carbonate on the heat exchanger surfaces with respect to the inhibition of crystal growth was conducted by Scanning Electron Microscope (SEM). The results showed that the formation of calcium carbonate crystals can be retarded significantly by adding MWCNT-DTPA additives as inhibition in the solution. Moreover, investigation was extended by introducing a non-invasive-monitoring of concentrations of calcium hardness in cooling water. Investigation was conducted with a 2.5 GHz microwave cavity resonator. The principle of electric dipole moment theories were used to analyse the sample solution that occurs as a function of calcium ion content. The sample was centrally positioned in the electric field of the TM010 mode of a resonant cylindrical cavity. COMSOL simulation package was used to compare and validate the experimental cavity resonator frequency. Transmission signal (S21) measurements via Vector Network Analyser (VNA) with different concentrations were investigated and observed linear relationship in amplitude with frequency changes. These researches successfully introduce a novel technique of monitoring of water hardness concentration by using non-invasive microwave sensor.